The Top-Viewed Cryosphere Videos on YouTube: An Overview - Adam Emmer; Vojtěch Cuřín; Jan Daněk; Helena Duchková; Petr Krpec (Geosciences, 2019)
Youtube.com has become one of the most popular places to share videos on the Internet, storing a large amount of audiovisual materials. People all over the world can upload their videos and watch videos of others. The research potential of this information source has received increasing popularity across scientific disciplines. In this contribution, we explore the top viewed videos containing selected cryospheric keywords, both general (cryosphere, glacier, ice, permafrost, snow), and specific, focusing on different types of cryospheric hazards (avalanche, blizzard and glacial lake outburst flood/jokulhlaup). Searching 100 top-viewed videos for each keyword, our database consists of 859 videos. Each video is described by several qualitative characteristics (e.g., video type, geographical focus) as well as quantitative characteristics (e.g., views per day, likes). A total of 310 videos in our database (36.1% of all) are classified as videos with factual cryospheric content. We show that the broader audience represented by YouTube users is particularly interested in videos capturing dynamic processes such as calving of glaciers. While videos found for general cryosphere keywords have attracted a generally higher attention of YouTube users (total views), videos found for specific keywords are ranked among the most liked. Further, we analyze where the videos with cryospheric content are filmed, revealing several hotspots for different keywords located in all continents except for Africa. Finally, we discuss the potentials of cryosphere videos for educational and research purposes, pointing out that videos filmed by incidental witnesses of low-frequency processes such as glacial lake outburst floods might contribute to the elucidation of their dynamics, magnitude and behavior as well as the occurrence in space and time.